Rancang Bangun Sistem Absensi Karyawan Berbasis Android Menggunakan Metode Waterfall Di Maxima Laundry - Reyner Albiando, Alfred; Eko Prasetyo, Bagas; Ananda, Fito; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
The development of information technology over the past five years has driven the digitalization of business processes, including in small and medium enterprises such as laundry services. Maxima Laundry, as a growing business, faces challenges in managing employee attendance manually and requires an efficient digital solution that can be accessed remotely. This study aims to design and develop an Android-based employee attendance system using the Waterfall methodology. The system is equipped with real-time attendance tracking features and location verification using GPS and IP address. The implementation results show that the system improves transparency, efficiency, and accuracy in attendance management. It also allows business owners to monitor employee presence remotely, even when residing abroad. Future development recommendations include the addition of security features and user training to enhance system effectiveness.